PENGELOLAAN DAN PEMBERIAN SANTUNAN DUKA - Asrifah . (Islamic Economic Law Programs, Faculty of Sharia and Law State Islamic University (UIN) of Sunan Ampel Surabaya., 2014)
Insurance is a group initially formed a social gathering that aims to ease the financial burden of individuals and fund financing difficulties. In the course of B'life Wadi>'ah Wise participants can choose their own future financial planning between annual, semiannual, quarterly and monthly with a very attractive profit. Also in B'life Wadi>'ahÂ Wise also provide compensations funds for participants or clients of the unfortunate death. This means that if the insurance period, participants (customers) of the unfortunate death, the beneficiary will receive compensations. In the course of BNI Life Insurance products issued B'life Wadi>'ah Wise gives compensations funds to participants of the unfortunate death even though premiums or funds provided but not enough larger compensations received, then the company is obliged to bail. In Islamic law granting compensations that are allowed, but giving compensations available at BNI insurance is life insurance in which there is an element of garar. Were not in accordance with the guiding principle of shari'ah> 'ah as in terms of invested funds compensations given greater of premiums or contributions.